Evolutionary relationships among Massospora spp. (Entomophthorales), obligate pathogens of cicadas. (1st November 2020) - Macias, Angie M.; Geiser, David M.; Stajich, Jason E.; Łukasik, Piotr; Veloso, Claudio; Bublitz, DeAnna C.; Berger, Matthew C.; Boyce, Greg R.; Hodge, Kathie; Kasson, Matt T.
ABSTRACT: The fungal genus Massospora (Zoopagomycota: Entomophthorales) includes more than a dozen obligate, sexually transmissible pathogenic species that infect cicadas (Hemiptera) worldwide. At least two species are known to produce psychoactive compounds during infection, which has garnered considerable interest for this enigmatic genus. As with many Entomophthorales, the evolutionary relationships and host associations of Massospora spp. are not well understood. The acquisition of M. diceroproctae from Arizona, M. tettigatis from Chile, and M. platypediae from California and Colorado provided an opportunity to conduct molecular phylogenetic analyses and morphological studies to investigate whether these fungi represent a monophyletic group and delimit species boundaries. In a three-locus phylogenetic analysis including the D1–D2 domains of the nuclear 28S rRNA gene (28S), elongation factor 1 alpha-like ( EFL ), and beta-tubulin ( BTUB ), Massospora was resolved in a strongly supported monophyletic group containing four well-supported genealogically exclusive lineages, based on two of three methods of phylogenetic inference. There was incongruence among the single-gene trees: two methods of phylogenetic inference recovered trees with either the same topology as the three-gene concatenated tree ( EFL ) or a basal polytomy (28S, BTUB ). Massospora levispora and M. platypediae isolates formed a single lineage in all analyses and are synonymized here as M. levispora. Massospora diceroproctae was sister to M. cicadina in all three single-gene trees and on an extremely long branch relative to the other Massospora, and even the outgroup taxa, which may reflect an accelerated rate of molecular evolution and/or incomplete taxon sampling. The results of the morphological study presented here indicate that spore measurements may not be phylogenetically or diagnostically informative. Despite recent advances in understanding the ecology of Massospora, much about its host range and diversity remains unexplored. The emerging phylogenetic framework can provide a foundation for exploring coevolutionary relationships with cicada hosts and the evolution of behavior-altering compounds.